It's a computation. It would be 8!/3!(8-3)! If my memory serves me correctly.
Answer:
(3, 2)
Step-by-step explanation:
Given the 2 equations
y = 2x - 4 → (1)
3x + y = 11 → (2)
Substitute y = 2x - 4 into (2)
3x + 2x - 4 = 11
5x - 4 = 11 ( add 4 to both sides )
5x = 15 ( divide both sides by 5 )
x = 3
Substitute x = 3 into (1) for corresponding value of y
y = (2 × 3) - 4 = 6 - 4 = 2
Solution is (3, 2)
You forgot to put the problem but choose answers that will divide evenly
Answer:
51 ft
Step-by-step explanation:
y-12 = -1/4 (x-3) = 51 ft